FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN EMESISGRAVIDARUM PADA IBU HAMIL TRIMESTER 1 DI RUMAH BERSALIN HASNA DEWI PEKANBARU - farianti, husna (UNIVERSITAS SARI MUTIARA INDONESIA, 2016)
Emesisgravidarum is one early signs of pregnancy 70 % pregnant woman had nausea and 28 % have been vomiting. Emesisgravidarum so often ignored because regarded as a consequence normal and physiological symptoms of a pregnancy , if they were seen from the other side emesisgravidarum make the negative impact for pregnant women and families. The purpose of this research is to analyze determine of emesisgravidarum for pregnant women in first trimester which parity, employment, pregnant knowledge, the use of contraceptive pill before pregnancy, and woman with the history of emesisgravidarum. The study type was analytical with cross-sectional approach. The Population in this study all of pregnant women first trimester visiting Maternity Homes Hasna Dewi in October – December 2015 (135 people), and samples 100 people using purposive sampling technique. The instrument used is questionaire. Data was analyzed by univariate analysis , bivariate analysis ( chi-square ) and multivariate analysis. Results of the study were calculated using statistical test Chi-Square showed all the factors influencing the emesisgravidarum among others, parity (P value 0.000), pregnant employment status (P Value 0.012), pregnant knowledge (P value 0.000), the use of contraceptive pill before pregnancy ( P value 0.011) and the history of emesisgravidarum ( P value 0.031). From the multivariate analysis of several factors which are the most dominant factor affecting the emesisgravidarum were parity (P value 0,052) OR 403,708. The midwife in antenatal care most considere all of the factor emesisgravidarum have to take care provided on and quality care.